2019
DOI: 10.21037/gs.2019.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of an automated breast volume scanner compared with a hand-held ultrasound: a meta-analysis

Abstract: Background: The diagnostic performance of an automated breast volume scanner (ABVS) compared with that of a hand-held ultrasound (HHUS) for breast cancer remains unclear. We performed a meta-analysis to compare the diagnostic performances of the ABVS and HHUS for breast cancer.Methods: We searched PubMed, EMBASE, Cochrane, and SinoMed databases to identify eligible studies up until November 14, 2018. Studies comparing ABVS and HHUS for differentiating benign and malignant breast tumors were included. A meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Our study showed that the sensitivity, specificity, accuracy, PPV and NPV of ABVS were slightly higher than HHUS. This finding was similar to previous studies 21 22 23 24 . ABVS can be more complete than HHUS for evaluating breast lesions because ABVS could improve breast lesion analysis by the additional coronal-plane imaging which provides for a better observation of lesion margin and each sectional plane of the saved volume can be visualized avoiding non-standardized documentation 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the sensitivity, specificity, accuracy, PPV and NPV of ABVS were slightly higher than HHUS. This finding was similar to previous studies 21 22 23 24 . ABVS can be more complete than HHUS for evaluating breast lesions because ABVS could improve breast lesion analysis by the additional coronal-plane imaging which provides for a better observation of lesion margin and each sectional plane of the saved volume can be visualized avoiding non-standardized documentation 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported that the performance of ABUS was comparable to that of hand-held ultrasound [20][21][22]. In addition, four prospective studies using ABUS demonstrated an increased cancer detection of 1.9-7.7 per 1000 examinations similar to hand-held ultrasound [10,11,14,23].…”
Section: Discussionmentioning
confidence: 98%
“…According to Lin X et al's study [6], the detection rate is up to 96%, but that of Niu L et al's [20] claims it is only 82%. A metaanalysis by Zhang X et al [21] revealed that HHUS produces a 90% rate with a large deviation that is closely related to the operator's diagnostic experience. In this study, we found that the AI-breast ultrasound reported a higher breast lesions rate than that conducted by general radiologists.…”
Section: Discussionmentioning
confidence: 99%